UMP strikes a partnership with Mercedes Benz Sdn. Bhd. - UMP, PNC
Universiti Malaysia Pahang (UMP) created history again when it signed a memorandum of understanding (MoU) with Mercedes Benz Sdn Bhd that paved the way for mutual cooperation in strengthening, promoting and developing areas in academic, research and development of the human capital on March 8, 2013.